1967
DOI: 10.1136/jcp.20.3.223
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age, sex, and diurnal variation on the human fibrinolytic system

Abstract: SYNOPSiS Fibrinolytic activity, as shown by the dilute blood clot lysis time, tends to show a diurnal variation, but is relatively unaffected by age and sex.Mean plasma anti-urokinase activity is consistently and significantly greater in females in the post-menstrual week than in age-matched males, but is relatively unaffected by daily variation and age. This sex difference in the activity of plasma, which is inhibitory to fibrinolysis, is of a degree which makes this measurement important in studies of the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1968
1968
1997
1997

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…However, our results indicated that the failure to demonstrate a difference could have resulted from using one resting sample taken early in the day as the basis for comparison or from studying an abbreviated diurnal response that did not include peak fluctuations (14,29). For example, if only 8 AM resting levels of fibrinolytic activity had been compared in the present study, it would have appeared that blood fibrinolytic activity was unaltered by the aging process (Table 1).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…However, our results indicated that the failure to demonstrate a difference could have resulted from using one resting sample taken early in the day as the basis for comparison or from studying an abbreviated diurnal response that did not include peak fluctuations (14,29). For example, if only 8 AM resting levels of fibrinolytic activity had been compared in the present study, it would have appeared that blood fibrinolytic activity was unaltered by the aging process (Table 1).…”
Section: Discussionmentioning
confidence: 69%
“…The conflicting results of several other studies (13,14,29) in which the effects of aging on fibrinolysis were examined may have been due, in some instances, to differences in the assay systems used to measure the fibrinolytic activity. However, our results indicated that the failure to demonstrate a difference could have resulted from using one resting sample taken early in the day as the basis for comparison or from studying an abbreviated diurnal response that did not include peak fluctuations (14,29).…”
Section: Discussionmentioning
confidence: 98%
“…Besides diurnal variation [Mann, 1967] several other factors like trauma, stress and physical exercise increase natural fibrinolytic activity in man [Fearnley, 1964]. The effect of these factors was not studied in the present investigations.…”
Section: Irfan Activation Of Fibrinolysis In Vivomentioning
confidence: 91%
“…[22][23][24] Plasminogen was estimated according to Alkjaersig et al 20 using the casein method. The results are expressed in percentages of normal.…”
mentioning
confidence: 99%